SATELLITE-BASED INSTRUCTIONAL MEDIA: A GLOBAL BROADCAST SYSTEM ANALYSIS WITH REGIONAL FOCUS ON INDIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This research investigates satellite-based educational communication with a focus on learning about and contrasting various broadcasting systems throughout the world, particularly as they pertain to India.